A day in the life of a carpenter - Burby, Liza N. (New York : PowerKids Press, 1999)
Describes the work of a carpenter who makes and repairs furniture.
Includes index.
Keywords: Carpentry -- Vocational guidance -- Juvenile literature; Carpenters -- Juvenile literature; Carpenters; Occupations